Potential for control of spoilage and mycotoxigenic species using mixtures of anti-oxidants, aliphatic acids and molecular approaches using RNAi - Leite, Goncalo M. (Cranfield University, 2013)
In recent years, consumer perceptions are that they would like minimum levels of preservatives or even preservative free food. However, this leads to higher risks of microbial spoilage problems, especially due to growth of spoilage fungi, which are capable of growth at intermediate environmental conditions. Studies have been carried out to evaluate the effect of different preservatives at optimal and sub-optimal concentrations on growth, biosynthesis of mycotoxin production at a molecular and phenotypic level for Fusarium graminearum (Tri5) and trichothecene production and Penicillium verrusocum (otapksPv) and ochratoxin A (OTA) production. These were complimented by studies on development of RNAi approaches to inhibit key regulatory genes in the biosynthetic pathways for mycotoxins in these two species. Additional studies were carried out to develop a rapid technique for RNA extraction from fungal biomass. Initial liquid media based studies identified the growth boundaries of a range of 20 spoilage fungi including 3 mycotoxigenic species in relation to preservatives and pH. This showed that up to the legal allowable concentrations of sorbic and benzoic salts at pH 3.0 all strains were capable of growth after 24h. With the exception of F. graminearum all the other species and strains of spoilage fungi were able to grow in these conditions. The use of a mixture of preservatives, a common practise in the food industry, proved effective at inhibiting growth of most spoilage fungi for 21 days at the EU legal limits. Over the EU legal limit of 250 ppm of potassium sorbate mixed with 150 ppm of sodium benzoate only Aspergillus niger had observable growth. Mixtures of weak organic acids, fumaric and malic acid, with the preservative potassium sorbate was shown to be effective at inhibiting growth below the legal limits of use of these food additives, even though the presence of potassium sorbate appears to be fundamental to the inhibition effect, of these natural food additives. Moreover the presence of fumaric acid stimulated growth of Aspergillus flavus. The extraction of high quality total RNA from low amounts of mycelium showed that up to 3 times higher yields can be achieved while improving RNA integrity and overall quality. This development also reduced the time required to extract fungal RNA and the risk of cross-contamination showing the potential use in high throughoutput gene expression studies. In vitro and In situ studies demonstrated the risk of using single sub-optimal antifungal compounds to inhibit growth and mycotoxin production. For F. graminearum, while growth was reduced, the Tri5 gene expression and trichothecenes type B production were stimulated in the presence of thyme essential oil, Prochloraz and BHA. This was also shown with P. verrucosum where otapksPv gene expression and OTA production were stimulated at different water conditions by the presence of sub-optimum concentrations of thyme essential oil and Prochloraz. The antioxidant BHA was able to reduce both otapksPv expression and OTA production in P. verrucosum. The use of siRNA oligonucleotides to silence Tri5 and otapksPv demonstrated that both F. graminearum and P. verrucosum possess the RNAi pathway machinery. In both mycotoxigenic fungi the expression of the target key biosynthetic pathway was knocked down. The optimum levels of the designed siRNA molecules were of between 10 and 25 nM for the molecules targeting P. verrucosum otapksPv. Even though gene silencing using siRNA molecules is transient the effect on otapksPv was still observable after 15 days. This lead to a 3 to 5 times a reduction in the amount of OTA. On the other hand, the silencing of Tri5 in F. graminearum was only detectable in the first 6 days after transfection.